EFFECT OF MOTIVATION, SATISFACTION, WORK ETHIC AND ENVIRONMENT ON EMPLOYEE PERFORMANCE THE KLATEN REGENCY REGIONAL SECRETARIAT - zaenal arifin; Sudarwati Sudarwati; Istiatin Istiatin (Universitas Andi Djemma, 2023)
The purpose of this research is to determine the relationship between employee performance in the Regional Secretariat of Klaten Regency and factors like motivation, job satisfaction, work ethic, and work environment.This style of research makes use of a structured quantitative study strategy. The Regional Secretariat of Klaten Regency is home to 94 employees. In this study, 94 participants were selected using the Census technique. Collecting data with the use of a worksheet. Analyses of the data were performed using statistical methods such multiple linear regression testing, F tests, t tests, and coefficients of determination.Based on the numbers, it's clear that the Regional Secretariat of Klaten Regency benefits from a healthy dose of inspiration, positivity, hard work, and a pleasant office environment. The study's findings have informed efforts by the Regional Secretariat of Klaten Regency to boost morale, productivity, and the office environment. Employee output will increase and become superior as a result of this